Montenegro : Public Expenditure and Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The purpose of the assessment is to provide the Montenegrin authorities with an internationally-recognized benchmark evaluation of the performance of the Montenegrin Public Financial Management (PFM) systems in order that they may thereafter consider the systems' strengths and weaknesses and develop strategies to strengthen them. The assessment comes at a critical juncture. After double-digit growth in 2007, economic growth has slowed considerably. On the fiscal side, the boom contributed to fiscal surpluses which cannot be sustained in the current economic climate and additional challenges in fiscal management have emerged. The potential to contain recurrent expenditure and implement institutional reforms on the integration path will require increasing efficiency in public administration. The management of the surge in tax and other revenues represented a special challenge for the government particularly given the significant revenues realized from the-one-off foreign investment in privatized state-owned enterprises. The level of public debt, which had steadily decreased over the past few years will be more difficult to contain, particularly in view of the highly pro-cyclical nature of economic policies. The PEFA assessment focuses primarily on the national level of a country's PFM system. PFM improvements now under consideration could contribute substantially in responding to those challenges.